Determination of the magnitude of completeness, b value and a value for seismicity analysis in Khuvsgul region - Ganbaatar, Ariunaa; Sereenendorj, Odbayar (Mongolian Journal of Astronomy and Geophysics, 2024)
The main earthquake activity in the Khuvsgul region, which is the region of the northern part of the Khangai mountain range, is taking place from the west along the Busiin gol, Darkhad Khotgor, and Khuvsgul Lake. The Khuvsgul seismic activity zone is surrounded by the Tunk Basin and Lake Baikal expansion zone in the north, and the Bulnai and Tsetserleg main faults, as well as weak and strong earthquakes, are still recorded. Therefore, a statistical mode study was carried out in the local earthquake catalogue (1964-2023) of this region with high seismic activity (Busiin gol, Darkhad Khotgor, Khuvsgul Lake) to check the magnitude completeness (Mc) value of the seismic database of the region. The corresponding ’a’ and ’b’ values of earthquake activity and frequency were determined by the seismic analysis program ’ZMAP’. According to the analysis, the magnitude completeness (Mc) evaluated by frequency magnitude distribution in the per unit area of the Khuvsgul region ranges from 1.3 to 2.1. The value of earthquake activity is a=4.880-5.775, which is high activity, and the frequency of strong earthquakes is b=0.81-0.90, which indicates that the seismic stress is accumulated in the region.